Perbandingan penerapan metode simulasi dan problem-based instructional untuk meningkatkan pemahaman siswa pada materi ekosistem - Irmayanti, Aulia; Damayanti, Rudiah; Wahyuni, Sri Ayu; Putra, Aminuddin Prahatama; Fajeriadi, Hery; Lisda, Lia Jumiati; Zaini, Muhammad; Nia, Dewi Ayu Aldilla (Journal of Bio-Creaducation, 2024)
Ecosystem material in science lessons is often poorly understood by students. This is because the learning method does not involve interaction between students and the material taught directly. This research aims to determine the level of students' understanding and activity in understanding the concept of ecosystem material using Problem-based instructional and Simulation methods. This research uses a nonequivalent control group design to compare the application of the Simulation method and the Problem-based instructional (PBI) method in Ecosystem learning for class X students at SMA Negeri Banjarmasin. The research population was all class X students of Banjarmasin State High School. The samples used were one class X MIPA which applied the simulation method as the experimental class, and another one class X MIPA which applied the Problem-based instructional method as the control class. Based on the results, the average posttest score for the experimental class with the Problem-based instructional method was 83.91, while the simulation method class was 77.78. This shows that both methods are equally good, but the Problem-based instructional method is superior to the simulation method. This research data shows significant value. The number of students who gave positive responses to the Problem-based instructional and simulation methods was 94.44% of students interested in participating in learning activities. This makes students enthusiastic when taking part in learning, students feel that learning seems more fun and not monotonous. The application of the Problem-based instructional and simulation method makes students understand the material being studied so that learning outcomes become more optimal.Materi Ekosistem pada pelajara IPA seringkali kurang dipahami oleh siswa. Hal tersebut dikarenakan metode pembelajaran yang kurang melibatkan interaksi antara siswa dengan materi yang diajarkan secara langsung. Penelitian ini bertujuan untuk mengetahui tingkat pemahaman dan aktivitas siswa dalam memahami konsep materi ekosistem dengan menggunakan metode Problem-based instructional dan Simulasi. Penelitian ini menggunakan desain nonequivalent control group design untuk membandingkan penerapan metode Simulasi dan metode Problem-based instructional (PBI) dalam pembelajaran Ekosistem pada siswa kelas X SMA Negeri Banjarmasin. Populasi penelitian adalah seluruh siswa kelas X SMA Negeri Banjarmasin. Sampel yang digunakan adalah satu kelas X MIPA yang diterapkan metode simulasi sebagai kelas eksperimen, dan satu lagi kelas X MIPA yang diterapkan metode Problem-based instructional sebagai kelas kontrol. Berdasarkan hasil rata-rata nilai posttest kelas eksperimen metode Problem-based instructional 83,91 sedangkan kelas metode simulasi 77,78. Hal ini menunjukkan bahwa kedua metode tersebut sama-sama bagus, namun metode Problem-based instructional lebih unggul dari metode simulasi. Data penelitian ini menunjukkan nilai signifikan. Jumlah siswa yang memberi tanggapan positif terhadap metode Problem-based instructional dan simulasi, sebesar 94,44% siswa tertarik mengikuti kegiatan pembelajaran. Hal ini menjadikan siswa bersemangat saat mengikuti pembelajaran, siswa merasa pembelajaran terkesan lebih menyenangkan dan tidak monoton. Penerapan metode Problem-based instructional dan simulasi membuat siswa paham terhadap materi yang dipelajari sehingga hasil belajar menjadi lebih optimal.